(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The paper is study of College Libraries in Mizoram with regard to its different physical resources With the result of trifurcation of Education Department, administration of the Colleges was taken over by the Department of Higher & Technical Education, Govt. of Mizoram since 1989. At present there are 24 degree colleges in Mizoram under the state government, each college has its own library which were started with without library professionals. Most of the College Libraries have no adequate library staff, some libraries does not have professional or semi professional or non-professional staff and are manage by only one or two library staff. Many colleges are running their library without Library Committee; as a result the college library developments could not go fast as it ought to be. All responsibilities of the administration of the college including library administration rest on the college Principal. A study had been conducted on the physical resources of different College Libraries in Mizoram This paper is a study of Library physical resources that include land, library building, book shelves, furniture, like chairs, tables, reading tables, reading rooms, racks etc. Physical Resources also includes ICT infrastructure like Computer, library software, Scanner, RFID technology, photocopier, Internet connection, LCD projector and other equipments.